2014
DOI: 10.1016/j.electacta.2013.08.105
|View full text |Cite
|
Sign up to set email alerts
|

Macro and micro aspects of the transport of chlorides in cementitious membranes

Abstract: A study of the transport of chlorides through hardened Portland cement paste membranes is reported. The flux of chlorides was induced by migration (AC and DC fields) and diffusion.Two parallel studies were developed. A macroscopic one where the migration of chlorides was followed by Electrochemical Impedance Spectroscopy (EIS) and a microscopic one in which the natural diffusion was investigated using the scanning electrochemical microscopy (SECM). Both studies have revealed to be complementary. The local inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Therefore as the ionic content is being reduced, the resistance increases and the electrical current that flows through the sample, when a constant voltage is applied, should decrease as indicated in [9,23,24,26].…”
Section: Ion Mobilization Using the Intensity And Resistance Measuremmentioning
confidence: 97%
“…Therefore as the ionic content is being reduced, the resistance increases and the electrical current that flows through the sample, when a constant voltage is applied, should decrease as indicated in [9,23,24,26].…”
Section: Ion Mobilization Using the Intensity And Resistance Measuremmentioning
confidence: 97%
“…Many researchers [43][44][45][46] simulated the electric field distribution in cement sample. B. Díaz et al 43 simulated the influence of cell geometry on the measurement of resistivity of the cement-based materials, and found that the effect of the electric field distribution is a function of the resistivity.…”
Section: Fundamental Theory For Four-point and Two-point Measurement mentioning
confidence: 99%
“…Previous studies have defined the concept of critical chloride threshold, beyond which steel rebars will be depassivated . In addition, the transport mechanism of chloride ions through cement‐based materials has been fully studied . Therefore, it is possible to predict the initial time for the depassivation of steel rebars caused only by chloride ingress …”
Section: Introductionmentioning
confidence: 99%